Designing R-Funlish For 11th Grade Students At SMK Kreatif (SCHOOLAR: Social and Literature Study in Education, 2024)
English language learning is developing English skills contextually and gratefully according to the context and daily condition and situation of students. This is to produce a form of English learning that touches more on the language needs of learners. This research is aimed at designing a learning media called R_Funlish (Reading Fun English) application for 11th grade students at SMK Kreatif Hasbullah Bahrul Ulum Tanbakberas Jombang. Especially in reading skill material. This research discusses the media for learning reading skills based on Google Drive Hyperlink as media to support teaching and learning activities. This research uses Research & Development with ADDIE models which consist of five stages such as analysis, Design, Development, Implementation, and Evaluation. The subject of research is the eleventh-grade students in SMK Kreatif Hasbullah Bahrul Ulum Tambakberas Jombang. 1). The result of media validation was 89,4 (very good), 2). the result of material validation was  (good), and 3). the result of the respondent was 85,18 (very good). Based on the result of the study, R_Funlish application shows that the media can influence enthusiasm for learning and make them more excited about understanding the material.